UN Habitat's participatory initiative to public space design involving residents, refugees and local authorities: the case of Nabaa', Bourj Hammoud, Lebanon - Mady, Christine (AESOP, 2019)
This paper explores the process of engaging participants in designing a public space in a neighbourhood with socially deprived people from different backgrounds. The space was designed by locals and refugees, with the support of the local authorities. The paper investigates the extents to which placemaking, initiated by a third party could generate a civic space that combines people through everyday needs stemming from the context, and being addressed over time, rather than in a fixed design outcome. It examines the intervention initiated by UN Habitat Lebanon in Bourj Hammoud municipality at the eastern boundaries of administrative Beirut, and specifically within it, the area of Naba’a. Studying this public space initiative within Naba’a addresses marginal neighbourhoods that are in need of ameliorating the living conditions, and improving the quality of life for the population. UN Habitat’s intervention comprised mediation between municipality and residents, and collaboration with the local residents and refugees within one neighbourhood in Naba’a, and framing their needs for an open public space. UN Habitat engaged the municipality in supporting the locals in executing this public space. The presentation argues that this process enabled place attachment for people with no official claim to an urban area.
Keywords: public space; social cohesion; place attachment; Bourj Hammoud